Concept maps as a tool to help improve the quality of elementary school final years (Research, Society and Development, 2022)
The present study sought to demonstrate the possibilities regarding the use of Concept Maps in the Final Years of Elementary School, aiming at increasing the quality of teaching offered, as well as the impacts on meaningful learning and on the process of knowledge construction. A bibliographic research was carried out, with the aim of forming a theoretical basis on Conceptual Maps and their relationship with the teaching-learning process and with the protagonism of students in the construction of knowledge. Through the review, it was possible to observe that Concept Maps can act as an aid tool and a facilitator, whether for students or teachers.